Case Report: Metagenomic Next-Generation Sequencing Can Contribute to the Diagnosis and Treatment of Disseminated Visceral Kaposi Sarcoma Following Allogeneic Haematopoietic Stem Cell Transplantation - Zhou, Kuangguo; Xu, Jinhuan; Shang, Zhen; Sun, Hanying; Shen, Kefeng; Xiao, Yi (Frontiers in Oncology, 2022)
Disseminated visceral Kaposi sarcoma (KS) following allogeneic haematopoietic stem cell transplantation (HSCT) is a rare but life-threatening posttransplant complication. A suitable management strategy for disseminated KS involvement in transplant patients is unclear. Here, we reported a patient who developed disseminated visceral KS following HSCT, which was the first detailed report documenting the relationship among KS development, delayed immune reconstitution, and HHV-8 DNA levels by metagenomic next-generation sequencing (mNGS). The HHV-8 viral load peaked at 2071 sequence reads with an absolute lymphocyte count of 0.17×109/L on day +242. On day +536, the HHV-8 viral load became undetectable, with an absolute lymphocyte count of 1.06×109/L and the KS disappearance. HHV-8 load in blood detected by mNGS may be used as an early prediction marker for KS, a guide for early withdrawal of immunosuppression, and a tool to monitor KS treatment response in the setting of HSCT, especially in patients with CMV-seropositive or graft failure postengraftment. Through whole-exome sequencing, we explored the molecular mechanism underlying the patient’s longer latency of haematopoietic or immune reconstitution and recurrent infections. Germline mutations in the FANCI and RAD51 genes might impair the patient's DNA repair ability, leading to a degree of immunodeficiency and tumour susceptibility. We strongly recommended evaluating the clinical history of the donor and investigating whether there were possible germline mutations suspected for immunodeficiency or familiar neoplasms. Disseminated visceral KS patients could likely benefit from chemotherapy, especially if the disease appears to be aggressive.